2022
DOI: 10.3390/biomedicines10020510
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Human Gut Microbiota in Healthy Adults: A Systematic Review

Abstract: The intestinal microbiota is a crucial regulator of human health and disease because of its interactions with the immune system. Tobacco smoke also influences the human ecosystem with implications for disease development. This systematic review aims to analyze the available evidence, until June 2021, on the relationship between traditional and/or electronic cigarette smoking and intestinal microbiota in healthy human adults. Of the 2645 articles published in PubMed, Scopus, and Web of Science, 13 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…The gastrointestinal tract is significantly affected by smoking; in fact, in most of the studies cited, there are differences in the composition of the microbiota between smokers and non-smokers [ 55 , 56 , 57 , 58 , 59 ]. This finding is also confirmed by a recent systematic review [ 60 ].…”
Section: Resultssupporting
confidence: 87%
“…The gastrointestinal tract is significantly affected by smoking; in fact, in most of the studies cited, there are differences in the composition of the microbiota between smokers and non-smokers [ 55 , 56 , 57 , 58 , 59 ]. This finding is also confirmed by a recent systematic review [ 60 ].…”
Section: Resultssupporting
confidence: 87%
“…Toxic chemical exposure such as nicotine, aldehydes, polycyclic aromatic hydrocarbons result in intestinal irritation and impaired mucosal immune responses. Proteobacteria increase in number with high number of pack-years of cigarette smoking in systematic review [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed the effect of lifestyle habits, such as tobacco smoking and alcohol consumption on response to the anti-PD-1 therapy in our cohort. Cigarette smoking was found to impact both innate and adaptive immunity and affect gut microbiota composition [120,121]. Furthermore, several studies on NSCLC patients demonstrated improved clinical outcomes to the ICI therapy in smokers versus non-smokers, suggesting that smoking may contribute to higher immunogenicity and activation of the immune microenvironment [122,123].…”
Section: Discussionmentioning
confidence: 99%